2021
DOI: 10.3390/plants10020335
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cerium Oxide Nanoparticles on Two Terrestrial Wild Plant Species

Abstract: Most current studies on the relationships between plans and engineered nanomaterials (ENMs) are focused on food crops, while the effects on spontaneous plants have been neglected so far. However, from an ecological perspective, the ENMs impacts on the wild plants could have dire consequences on food webs and ecosystem services. Therefore, they should not be considered less critical. A pot trial was carried out in greenhouse conditions to evaluate the growth of Holcus lanatus L. (monocot) and Diplotaxis tenuifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 64 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Third, when more than one size of ceria NPs was investigated in these studies, the ceria NPs were usually observed to have higher phytotoxicity with lower concentrations. Examples include studies by Hernandez‐Viezcas et al ., [31] Zhang et al ., [39] and Lizzi et al [41] . Among all these studies which used commercial ceria NPs of sizes ≥6 nm or NPs with a fairly large size range, our current study demonstrated that smaller sub‐3‐nm ceria NPs could induce observable phytotoxicity at the lowest concentration (0.1 ppm).…”
Section: Resultsmentioning
confidence: 48%
“…Third, when more than one size of ceria NPs was investigated in these studies, the ceria NPs were usually observed to have higher phytotoxicity with lower concentrations. Examples include studies by Hernandez‐Viezcas et al ., [31] Zhang et al ., [39] and Lizzi et al [41] . Among all these studies which used commercial ceria NPs of sizes ≥6 nm or NPs with a fairly large size range, our current study demonstrated that smaller sub‐3‐nm ceria NPs could induce observable phytotoxicity at the lowest concentration (0.1 ppm).…”
Section: Resultsmentioning
confidence: 48%
“…The application of CeO 2 -NPs through difference sources and concentrations has some beneficial effects on plants ( Cao et al., 2017 ; Fox et al., 2020 ; Lizzi et al., 2021 ), but the generalized effects cannot be defined at once due to the divergence in the effects of bulk and ionic parts of cerium ( Zhang et al., 2015 ; Barrios et al., 2016 ; Lizzi et al., 2021 ). The size of CeO 2 -NPs can limit their entry into plant cells as membrane pore size can reduce the translocation of NPs via cross root epidermal cell membranes ( Ma et al., 2010a ; Ma et al., 2010b ; Rico et al., 2011 ), where these NPs tend to adopt apoplastic pathways.…”
Section: Discussionmentioning
confidence: 99%